Fungsi Tortor Parsiarabu di Desa Salaon Kecamatan Ronggurnihuta Kabupaten Samosir - Magdalena Dina Sifra (Universitas Negeri Medan, 2016)
This study discusses the function of the Parsiarabu in the village of Salaon TortorSubdistrict Rongurnihuta Samosir Regency.Landasan teoritis yang digunakandalam penelitian in] yaitu Teori Fungsi menurut Danesi.The theoretical foundation that is used in this study i.e. the theory of Functionaccording to Danesi people who live in the village of Salaon sub-district ofRonggurnihuta Samosir Regency. Data collection is done by the method of fieldwork which includes some steps i.e. interview, direct observation, documentationand library studies. The methods used in the research is qualitative, descriptivemethods.Research results based on the data collected can be known that Tortor Parsiarahuis the life story of Batak Toba at partonun on Samosir formerly, especiallywives who had left her husband and wife where the husband lost when taking ofarabu ulos dye in the forest. From there it became a habit for a group ofmasyarakatan partonun in one village where each host na mabalu (the wifewho had lost husbands) then the family whose husband died will hold themanortor Parsiarabu where Tortor is the wife who has lost her husband to entertaintheir friends who recently lost her husband in order to rise from sorrow.